Giraffa camelopardalis: limb bone histology through ontogeny - Smith, Caitlin Caryl Danielle (Department of Biological Sciences, 2020)
Although there are many studies on mammalian bone histology, there are only a few that have examined the bone histology of artiodactyls, or focused specifically on osteohistological changes during ontogeny. The current study investigates the microanatomy and histology of giraffe limb bones through ontogeny. Mid-diaphyseal sections of humeri, radii, metacarpals, femora, and tibiae of 14 individuals representing individuals of known sex, as well as at different ontogenetic stages (foetal, juveniles, subadults, and adults). Thin sections were prepared for all the bones, and microanatomical (using Bone Profiler) and histological analyses were conducted on each of the sections. The study examined three main aspects, 1) Crosssectional shape changes in limb bones through ontogeny, 2) Histological changes through ontogeny in each of the limb bones, and 3) Histovariability among skeletons. The results of the study show that the foetus and juvenile individuals have round cross-sections, with small vacant medullary cavities, while cross sections of older individuals tend to be oval with variable amounts of cancellous bone surrounding the medullary cavity. The highest bone compactness values were obtained for the humerus and femur of the foetus, whereas the radius, metacarpal, and tibia bone compactness values are similar across the age classes. In terms of histology, this study found that the earlier ontogenetic stages had highly vascularised fibrolamellar bone in their cortices, which contrasts with that of the subadults and adults where more slowly deposited bone tissue occurs. These observations indicate that after rapid initial growth during early ontogeny, osteogenesis (and overall growth) slows down. This research also documents the fusion of the metacarpal III and IV, and the associated changes that occur in the histology. The study also highlights that the tibia is the only bone that has long radial vascular canals in the cortex. Overall the results of this study have provided a much better understanding of the bone histology of giraffes during ontogeny and has therefore filled an important gap in our knowledge of mammalian bone tissues. Furthermore, this study has direct implications for any future palaeohistological studies of fossil giraffids from Langebaanweg in South Africa.